A light-converting solar cell encapsulation adhesive film and preparation method thereof
By using full-spectrum white light-emitting carbon quantum dots as the photoconverter in the photovoltaic packaging film, the problems of low solar light utilization efficiency and material safety risks in the prior art are solved, and more efficient solar cell performance and safer material selection are achieved.
Patent Information
- Application Number
- CN202310255379.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-16
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-03-16
AI Technical Summary
The existing photovoltaic packaging films have low efficiency in utilization of sunlight, and commonly used photoconverters have environmental risks, PID risks caused by metal particles precipitation, and the problems of organic ligands being easily discolored.
Full-spectrum white light-emitting carbon quantum dots are used as the light conversion agent. This carbon quantum dot can convert ultraviolet light into 400-700nm full-spectrum white visible light, free of metal elements and organic ligands, avoiding related risks.
The utilization efficiency of solar cells on sunlight is improved, and there is no problem of metal particles precipitation and organic ligand discoloration, and the process is simple and feasible.
Smart Images

Figure CN116355547B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of packaging adhesive films for solar cell components, and in particular to a light-converting solar cell packaging adhesive film and a preparation method thereof. Background Art
[0002] Due to the human demand for affordable clean energy, solar photovoltaic power generation based on the photoelectric conversion effect is rapidly entering the human energy structure and gradually becoming the main clean energy. At present, crystalline silicon cells are the main application form of solar photovoltaic power generation, and the photoelectric conversion efficiency of its actual industrialized photovoltaic modules is only about 18%. In addition to the low physical conversion effect of crystalline silicon cells themselves, another important reason is that this type of cell technology only responds to sunlight with a wavelength range of 400-1100nm. Sunlight with a wavelength less than 400nm and greater than 1100nm can hardly be absorbed and utilized by the cell, resulting in energy loss.
[0003] To solve the above problems, there are two main academic and industry methods. One is to improve the structure of solar cells themselves, but this involves the elimination and updating of new and old technologies in the entire industrial chain, which is difficult to promote. The other is to add substances with light conversion effects to the photovoltaic encapsulation film to convert light in the ultraviolet band into light in the visible light band, so that it can be absorbed and utilized by solar cells, thereby improving the power generation efficiency. This method is relatively simple to promote and can fully utilize existing production technology and equipment. Therefore, it has received widespread attention and interest.
[0004] The photoconverters currently used in photovoltaic encapsulation films mainly include rare earth-organic ligand complexes and semiconductor quantum dots. Rare earth-organic ligands as photoconverters for films have problems such as uneven dispersion, narrow absorption bands, low conversion efficiency, and easy discoloration of organic ligands after long-term use. Semiconductor quantum dots (such as CdS, CdTe, etc.) as photovoltaic film converters have environmental risks and PID risks caused by the precipitation of metal particles. In addition, the above two photoconverters can only convert the absorbed ultraviolet light into red or blue light with a narrow specific wavelength range, resulting in low battery utilization efficiency. Summary of the invention
[0005] In order to solve the technical problem of low utilization efficiency of sunlight by existing photovoltaic encapsulation films, the present invention provides a light-converting solar cell encapsulation film and a preparation method thereof. The encapsulation film uses specially prepared carbon quantum dots that can convert ultraviolet light into 400-700nm full-spectrum white visible light and do not contain metal elements and organic ligands, which can give solar cells a higher sunlight utilization efficiency, and there is no PID risk caused by the precipitation of metal particles, and there will be no problem of long-term discoloration of organic ligands.
[0006] The specific technical scheme of the present invention is:
[0007] In a first aspect, the present invention provides a light-converting solar cell encapsulation film, wherein the light-converting solar cell encapsulation film contains full-spectrum white light emitting carbon quantum dots; a method for preparing the full-spectrum white light emitting carbon quantum dots comprises the following steps:
[0008] (1) dissolving p-phenylenediamine in anhydrous ethanol to prepare a p-phenylenediamine ethanol solution with a concentration of 1-5 wt%;
[0009] (2) subjecting the p-phenylenediamine ethanol solution to a solvothermal reaction at 175-185° C. for 10-13 hours to obtain a reaction mixture;
[0010] (3) Using a mixture of methanol and dichloromethane in a volume ratio of 1:3.5-4.5 as an eluent, the reaction mixture is separated and purified by a gel permeation chromatography column, and the obtained eluate is extracted with water to obtain a dichloromethane solution containing full-spectrum white light emitting carbon quantum dots.
[0011] Carbon quantum dots have photoluminescent properties and can show fluorescence properties when stimulated by external excitation light sources. They are expected to be used as light conversion agents in the encapsulation film of light-converting solar cells. However, the luminescence mechanism of carbon quantum dots is complex and is still a topic of debate. There is no commonly accepted explanation yet, which makes it difficult to summarize, generalize, and discover obvious rules in the regulation of the fluorescence properties of carbon quantum dots. The carbon source, solvent, reaction conditions, separation and purification methods used in the preparation of carbon quantum dots will affect the fluorescence properties of the final carbon quantum dots. However, in the absence of regular guidance and poor predictability, it is difficult to obtain carbon quantum dots with the required specific emission wavelength.
[0012] After theoretical research and a large number of experiments, the team of the present invention found that the carbon quantum dots obtained by the preparation method of the above steps (1) to (3) can convert ultraviolet light with a wavelength of 300-400nm into full-spectrum white visible light of 400-700nm. Therefore, when it is applied to the light-converting solar cell encapsulation film, the utilization efficiency of solar cells for sunlight can be improved by utilizing its wider emission wavelength range. In addition, although it is possible to achieve a wider emission wavelength range by mixing multiple carbon quantum dots, due to the difference in performance between different carbon quantum dots, this mixture is easy to change color with time loss. The present invention uses a single carbon quantum dot to achieve full-spectrum white visible light emission, so the above problem will not occur.
[0013] In addition to the wide wavelength range of the carbon quantum dots emitting light, the preparation method of the full-spectrum white light emitting carbon quantum dots in the present invention also has the following advantages: (1) No metal elements or organic ligands are introduced during the preparation process. Therefore, when the prepared carbon quantum dots are used in the encapsulation film, there is no PID risk caused by the precipitation of metal particles, and there is no problem of long-term discoloration of organic ligands. (2) The carbon quantum dots prepared by the present invention have organic functional groups on the surface, have good compatibility with the encapsulation film, and have good solubility in organic solvents. When preparing the encapsulation film, they can fully penetrate into the matrix resin with the organic solvent. At the same time, this type of carbon quantum dots also has the advantages of good light transmittance and light stability, which is conducive to giving solar cells a higher solar light utilization efficiency. (3) The preparation process is simple and can be produced using existing mature industrial equipment.
[0014] Preferably, in step (3), the filler in the gel permeation chromatography column is silica gel with a mesh size of 200-300 meshes.
[0015] Preferably, after step (3), the solvent in the dichloromethane solution containing the full-spectrum white light emitting carbon quantum dots is evaporated to obtain a full-spectrum white light emitting carbon quantum dot powder.
[0016] Preferably, the raw materials of the light-converting solar cell encapsulation film include the following components in parts by weight: 100 parts of base resin, 0.05-0.5 parts of full-spectrum white light emitting carbon quantum dot solution, and 0.1-2 parts of cross-linking agent.
[0017] Using a full-spectrum white light emitting carbon quantum dot solution as a raw material is conducive to the carbon quantum dots penetrating into the resin along with the solvent, so that the carbon quantum dots are evenly distributed in the final light-converting solar cell encapsulation film.
[0018] Furthermore, in the full-spectrum white light emitting carbon quantum dot solution, the content of full-spectrum white light emitting carbon quantum dots is 3-10wt%.
[0019] Furthermore, the solvent in the full-spectrum white light emitting carbon quantum dot solution is dichloromethane.
[0020] When the solvent used is dichloromethane, after obtaining the dichloromethane solution containing full-spectrum white light emitting carbon quantum dots through steps (1) to (3), the solvent does not need to be evaporated and can be directly used for the preparation of the encapsulation film or can be concentrated to the required concentration.
[0021] Furthermore, the raw materials of the light-converting solar cell encapsulation film also include the following components in parts by weight: 0.1-2 parts of a cross-linking agent, 0.1-2 parts of a coupling agent, 0.01-1 parts of a light stabilizer, and 0.01-2 parts of an antioxidant.
[0022] Furthermore, the base resin is one or more of ethylene-vinyl acetate copolymer, ethylene-octene copolymer, ethylene-butene copolymer, ethylene-methyl methacrylate copolymer and polyvinyl butyral.
[0023] Furthermore, the resin melt index of the ethylene-vinyl acetate copolymer is 5-60g / 10min, wherein the content of vinyl acetate is 25-35wt%; the resin melt index of the ethylene-octene copolymer or ethylene-butene copolymer is 2-40g / 10min, wherein the content of octene or butene is 15-50wt%.
[0024] Further, the cross-linking agent is one or more of tert-butyl peroxycarbonate-2-ethylhexyl ester, tert-amyl peroxy (2-ethylhexyl) carbonate, tert-butyl peroxybenzoate, tert-butyl peroxyacetate, tert-amyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate and diisopropylbenzene peroxide.
[0025] Furthermore, the auxiliary cross-linking agent is one or more of triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, trimethylolpropane triethoxyacrylate and triallyl isocyanate.
[0026] Furthermore, the coupling agent is one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri(β-methoxyethoxy) silane, γ-methacryloxypropyl trimethoxy silane and vinyl tri-tert-butoxy silane.
[0027] Furthermore, the light stabilizer is one or more of bis-2,2,6,6-tetramethylpiperidinol sebacate, poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) succinate and bis(2,2,6,6-tetramethyl-4-piperidinol) sebacate.
[0028] Furthermore, the antioxidant is one or more of antioxidant 1010 , antioxidant 168 , antioxidant 1076 , antioxidant 626 and antioxidant 1024 .
[0029] In a second aspect, the present invention provides a method for preparing the light-converting solar cell encapsulation film, comprising the following steps:
[0030] S1: Mix all raw materials and remove the solvent to obtain masterbatch;
[0031] S2: Extruding and molding the masterbatch to obtain a light-converting solar cell encapsulation film.
[0032] Furthermore, the solvent in the full-spectrum white light emitting carbon quantum dot solution is dichloromethane; in step S1, the method of mixing and removing dichloromethane is stirring at 40-50°C.
[0033] Compared with the prior art, the present invention has the following advantages:
[0034] (1) The carbon quantum dots obtained by the method of the present invention can convert ultraviolet light with a wavelength of 300-400nm into full-spectrum white visible light of 400-700nm, so when used in the light-converting solar cell encapsulation film, they can give the solar cell a higher sunlight utilization efficiency;
[0035] (2) The carbon quantum dots obtained by the method of the present invention do not contain metal elements and organic ligands. Therefore, when used in the light-converting solar cell encapsulation film, there is no PID risk caused by the precipitation of metal particles, and there is no problem of organic ligands being prone to discoloration due to long-term use. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is the emission spectrum of the concentrated full-spectrum white light emitting carbon quantum dot solution in Preparation Example 1.
[0037] Figure 2 It is the emission spectra of the solutions containing carbon quantum dots before concentration in Preparation Example 1, Comparative Preparation Example 1 and Comparative Preparation Example 2. Implementation
[0038] The present invention will be further described below in conjunction with the embodiments.
[0039] Overall embodiment
[0040] A light-converting solar cell encapsulation adhesive film, wherein the light-converting solar cell encapsulation adhesive film contains full-spectrum white light emitting carbon quantum dots; a preparation method of the full-spectrum white light emitting carbon quantum dots comprises the following steps:
[0041] (1) dissolving p-phenylenediamine in anhydrous ethanol to prepare a p-phenylenediamine ethanol solution with a concentration of 1-5 wt%;
[0042] (2) subjecting the p-phenylenediamine ethanol solution to a solvothermal reaction at 175-185° C. for 10-13 hours to obtain a reaction mixture;
[0043] (3) Using a mixture of methanol and dichloromethane in a volume ratio of 1:3.5-4.5 as an eluent, the reaction mixture is separated and purified by a gel permeation chromatography column, and the obtained eluate is extracted with water to obtain a dichloromethane solution containing full-spectrum white light emitting carbon quantum dots.
[0044] As a specific implementation, in step (3), the filler in the gel permeation chromatography column is silica gel with a mesh size of 200-300 meshes.
[0045] As a specific implementation, after step (3), the solvent in the dichloromethane solution containing the full-spectrum white light emitting carbon quantum dots is evaporated to obtain a full-spectrum white light emitting carbon quantum dot powder.
[0046] As a specific implementation manner, the raw materials of the light-converting solar cell encapsulation film include the following components in parts by weight: 100 parts of base resin, 0.05-0.5 parts of full-spectrum white light emitting carbon quantum dot solution, 0.1-2 parts of cross-linking agent, 0.1-2 parts of auxiliary cross-linking agent, 0.1-2 parts of coupling agent, 0.01-1 parts of light stabilizer, and 0.01-2 parts of antioxidant; in the full-spectrum white light emitting carbon quantum dot solution, the solvent is dichloromethane, and the content of full-spectrum white light emitting carbon quantum dots is 3-10wt%.
[0047] As a specific implementation, the method for preparing the light-converting solar cell encapsulation film comprises the following steps:
[0048] S1: Stir and mix all the raw materials at 40-50°C and remove the solvent to obtain a masterbatch;
[0049] S2: Extruding and molding the masterbatch to obtain a light-converting solar cell encapsulation film.
[0050] Optionally, the matrix resin is one or more of ethylene-vinyl acetate copolymer, ethylene-octene copolymer, ethylene-butene copolymer, ethylene-methyl methacrylate copolymer and polyvinyl butyral; the resin melt index of the ethylene-vinyl acetate copolymer is 5-60g / 10min, wherein the content of vinyl acetate is 25-35wt%; the resin melt index of the ethylene-octene copolymer or ethylene-butene copolymer is 2-40g / 10min, wherein the content of octene or butene is 15-50wt%.
[0051] Optionally, the crosslinking agent is one or more of tert-butyl peroxycarbonate-2-ethylhexyl ester, tert-amyl peroxy (2-ethylhexyl) carbonate, tert-butyl peroxybenzoate, tert-butyl peroxyacetate, tert-amyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate and dicumyl peroxide.
[0052] Optionally, the auxiliary cross-linking agent is one or more of triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, trimethylolpropane triethoxyacrylate and triallyl isocyanate.
[0053] Optionally, the coupling agent is one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri(β-methoxyethoxy) silane, γ-methacryloxypropyl trimethoxy silane and vinyl tri-tert-butoxy silane.
[0054] Optionally, the light stabilizer is one or more of bis-2,2,6,6-tetramethylpiperidinol sebacate, poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) succinate and bis(2,2,6,6-tetramethyl-4-piperidinol) sebacate.
[0055] Optionally, the antioxidant is one or more of antioxidant 1010 , antioxidant 168 , antioxidant 1076 , antioxidant 626 and antioxidant 1024 .
[0056] Preparation Example 1
[0057] Prepare a full spectrum white light emitting carbon quantum dot solution by the following steps:
[0058] (1) dissolving p-phenylenediamine in anhydrous ethanol to obtain a p-phenylenediamine ethanol solution with a concentration of 2 wt %;
[0059] (2) placing the p-phenylenediamine ethanol solution into a pressure-resistant reactor, subjecting it to solvent thermal treatment at 180° C. for 12 hours, and obtaining a uniform reaction mixture after cooling;
[0060] (3) Separating and purifying the reaction mixture by gel permeation chromatography, wherein the size of the gel permeation chromatography column is 400 mm×25 mm, the filler is silica gel with a mesh size of 200-300 mesh, and the eluent is a mixture of methanol and dichloromethane with a volume ratio of 1:4;
[0061] (4) The eluate is extracted with water to obtain a dichloromethane solution containing full-spectrum white light emitting carbon quantum dots. After concentrating and removing part of the dichloromethane, a 5 wt % full-spectrum white light emitting carbon quantum dot solution is obtained for standby use.
[0062] The full-spectrum white light emitting carbon quantum dot solution obtained after concentration in this preparation example was irradiated with ultraviolet light with a wavelength of 365 nm. The emission spectrum is as follows: Figure 1 As shown. Figure 1 It can be seen that the carbon quantum dots obtained in this preparation example can convert ultraviolet light into 400-700nm full-spectrum white light.
[0063] Preparation Example 2
[0064] Prepare a full spectrum white light emitting carbon quantum dot solution by the following steps:
[0065] (1) dissolving p-phenylenediamine in anhydrous ethanol to obtain a p-phenylenediamine ethanol solution with a concentration of 1 wt %;
[0066] (2) placing the p-phenylenediamine ethanol solution into a pressure-resistant reactor, subjecting it to solvent thermal treatment at 175° C. for 13 hours, and obtaining a uniform reaction mixture after cooling;
[0067] (3) Separating and purifying the reaction mixture by gel permeation chromatography, wherein the size of the gel permeation chromatography column is 400 mm×25 mm, the filler is silica gel with a mesh size of 200-300 mesh, and the eluent is a mixture of methanol and dichloromethane with a volume ratio of 1:3.5;
[0068] (4) The eluate is extracted with water to obtain a dichloromethane solution containing full-spectrum white light emitting carbon quantum dots. After concentrating and removing part of the dichloromethane, a 5 wt % full-spectrum white light emitting carbon quantum dot solution is obtained for standby use.
[0069] After testing, it was found that the carbon quantum dots obtained in this preparation example can convert ultraviolet light into 400-700nm full-spectrum white light.
[0070] Preparation Example 3
[0071] Prepare a full spectrum white light emitting carbon quantum dot solution by the following steps:
[0072] (1) dissolving p-phenylenediamine in anhydrous ethanol to obtain a p-phenylenediamine ethanol solution with a concentration of 5 wt %;
[0073] (2) placing the p-phenylenediamine ethanol solution into a pressure-resistant reactor, subjecting it to solvent thermal treatment at 185° C. for 10 hours, and obtaining a uniform reaction mixture after cooling;
[0074] (3) Separating and purifying the reaction mixture by gel permeation chromatography, wherein the size of the gel permeation chromatography column is 400 mm×25 mm, the filler is silica gel with a mesh size of 200-300 mesh, and the eluent is a mixture of methanol and dichloromethane with a volume ratio of 1:4.5;
[0075] (4) The eluate is extracted with water to obtain a dichloromethane solution containing full-spectrum white light emitting carbon quantum dots. After concentrating and removing part of the dichloromethane, a 5 wt % full-spectrum white light emitting carbon quantum dot solution is obtained for standby use.
[0076] After testing, it was found that the carbon quantum dots obtained in this preparation example can convert ultraviolet light into 400-700nm full-spectrum white light.
[0077] Comparative Preparation Example 1
[0078] The specific operation steps of this comparative preparation example are the same as those of Preparation Example 1, and the only difference from Preparation Example 1 is that in step (4), the eluent is not subjected to water extraction, but is directly concentrated to obtain a 5 wt % carbon quantum dot solution for standby use.
[0079] Comparative Preparation Example 2
[0080] The specific operating steps of this comparative preparation example are the same as those of Preparation Example 1, and the only difference from Preparation Example 1 is that in step (4), after the eluent is extracted with water, the obtained aqueous phase (i.e., a mixed solution of methanol and water containing hydrophilic carbon quantum dots) is taken, and after concentrating and removing part of the methanol and water, a 5 wt % carbon quantum dot solution is obtained for standby use.
[0081] The solutions containing carbon quantum dots before concentration in Preparation Example 1, Comparative Preparation Example 1 and Comparative Preparation Example 2 were irradiated with ultraviolet light with a wavelength of 365 nm, and the emission spectra were shown in FIG. Figure 2 .from Figure 2 It can be seen that if water extraction is not performed after gel permeation chromatography or the aqueous phase is taken after water extraction, the obtained carbon quantum dots cannot emit white fluorescence under ultraviolet light (the former emits pink fluorescence).
[0082] Application Example 1
[0083] The full-spectrum white light emitting carbon quantum dot solution obtained in Preparation Example 1 is used to prepare a light-converting solar cell encapsulation film, and the specific steps are as follows:
[0084] S1: Weigh the following raw materials in parts by weight: 100 parts of POE resin (melt index of 15 g / 10 min, melting point of 76°C), 0.05 parts of full-spectrum white light emitting carbon quantum dot solution (obtained in Preparation Example 1), 1.0 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.8 parts of triallyl isocyanurate, 0.5 parts of γ-methacryloxypropyltrimethoxysilane, 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacate, and 0.1 parts of antioxidant 1076;
[0085] S2: Put all the raw materials into a mixing kettle, control the temperature at 45±5°C and stir and mix, so that the carbon quantum dots and other additives penetrate into the resin, and the low boiling point solvent dichloromethane gradually evaporates to obtain a masterbatch;
[0086] S3: The masterbatch is put into a single screw extruder for melt extrusion, and then put into a casting machine for casting molding, and then embossing, cooling, pulling and winding are performed in sequence to produce a light conversion solar cell encapsulation film with a thickness of 0.5 mm.
[0087] Application Example 2
[0088] The full-spectrum white light emitting carbon quantum dot solution obtained in Preparation Example 1 is used to prepare a light-converting solar cell encapsulation film, and the specific steps are as follows:
[0089] S1: Weigh the following raw materials in parts by weight: 100 parts of POE resin (melt index of 15 g / 10 min, melting point of 76°C), 0.1 parts of full-spectrum white light emitting carbon quantum dot solution (obtained in Preparation Example 1), 1.0 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.8 parts of triallyl isocyanurate, 0.5 parts of γ-methacryloxypropyltrimethoxysilane, 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacate, and 0.1 parts of antioxidant 1076;
[0090] S2: Put all the raw materials into a mixing kettle, control the temperature at 45±5°C and stir and mix, so that the carbon quantum dots and other additives penetrate into the resin, and the low boiling point solvent dichloromethane gradually evaporates to obtain a masterbatch;
[0091] S3: The masterbatch is put into a single screw extruder for melt extrusion, and then put into a casting machine for casting molding, and then embossing, cooling, pulling and winding are performed in sequence to produce a light conversion solar cell encapsulation film with a thickness of 0.5 mm.
[0092] Application Example 3
[0093] The full-spectrum white light emitting carbon quantum dot solution obtained in Preparation Example 1 is used to prepare a light-converting solar cell encapsulation film, and the specific steps are as follows:
[0094] S1: Weigh the following raw materials in parts by weight: 100 parts of POE resin (melt index of 15 g / 10 min, melting point of 76°C), 0.2 parts of full-spectrum white light emitting carbon quantum dot solution (obtained in Preparation Example 1), 1.0 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.8 parts of triallyl isocyanurate, 0.5 parts of γ-methacryloxypropyltrimethoxysilane, 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacate, and 0.1 parts of antioxidant 1076;
[0095] S2: Put all the raw materials into a mixing kettle, control the temperature at 45±5°C and stir and mix, so that the carbon quantum dots and other additives penetrate into the resin, and the low boiling point solvent dichloromethane gradually evaporates to obtain a masterbatch;
[0096] S3: The masterbatch is put into a single screw extruder for melt extrusion, and then put into a casting machine for casting molding, and then embossing, cooling, pulling and winding are performed in sequence to produce a light conversion solar cell encapsulation film with a thickness of 0.5 mm.
[0097] Application Example 4
[0098] The full-spectrum white light emitting carbon quantum dot solution obtained in Preparation Example 2 is used to prepare a light-converting solar cell encapsulation film, and the specific steps are as follows:
[0099] S1: Weigh the following raw materials in parts by weight: 100 parts of POE resin (melt index of 15 g / 10 min, melting point of 76°C), 0.05 parts of full-spectrum white light emitting carbon quantum dot solution (obtained in Preparation Example 2), 0.8 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.6 parts of triallyl isocyanurate, 0.5 parts of γ-methacryloxypropyltrimethoxysilane, 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacate, and 0.1 parts of antioxidant 1076;
[0100] S2: Put all the raw materials into a mixing kettle, control the temperature at 45±5°C and stir and mix, so that the carbon quantum dots and other additives penetrate into the resin, and the low boiling point solvent dichloromethane gradually evaporates to obtain a masterbatch;
[0101] S3: The masterbatch is put into a single screw extruder for melt extrusion, and then put into a casting machine for casting molding, and then embossing, cooling, pulling and winding are performed in sequence to produce a light conversion solar cell encapsulation film with a thickness of 0.5 mm.
[0102] Application Example 5
[0103] The full-spectrum white light emitting carbon quantum dot solution obtained in Preparation Example 3 is used to prepare a light-converting solar cell encapsulation film, and the specific steps are as follows:
[0104] S1: Weigh the following raw materials in parts by weight: 100 parts of POE resin (melt index of 15 g / 10 min, melting point of 76°C), 0.05 parts of full-spectrum white light emitting carbon quantum dot solution (obtained in Preparation Example 3), 1.0 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.6 parts of trimethylolpropane trimethacrylate, 0.5 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacate, and 0.1 parts of antioxidant 1076;
[0105] S2: Put all the raw materials into a mixing kettle, control the temperature at 45±5°C and stir and mix, so that the carbon quantum dots and other additives penetrate into the resin, and the low boiling point solvent dichloromethane gradually evaporates to obtain a masterbatch;
[0106] S3: The masterbatch is put into a single screw extruder for melt extrusion, and then put into a casting machine for casting molding, and then embossing, cooling, pulling and winding are performed in sequence to produce a light conversion solar cell encapsulation film with a thickness of 0.5 mm.
[0107] Application Example 6
[0108] The full-spectrum white light emitting carbon quantum dot solution obtained in Preparation Example 1 is used to prepare a light-converting solar cell encapsulation film, and the specific steps are as follows:
[0109] S1: Weigh the following raw materials in parts by weight: 100 parts of POE resin (melt index of 15 g / 10 min, melting point of 76° C.), 0.05 parts of full-spectrum white light emitting carbon quantum dot solution (obtained in Preparation Example 1), 0.8 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.5 parts of triallyl isocyanurate, 0.5 parts of γ-methacryloxypropyltrimethoxysilane, and 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacate;
[0110] S2: Put all the raw materials into a mixing kettle, control the temperature at 45±5°C and stir and mix, so that the carbon quantum dots and other additives penetrate into the resin, and the low boiling point solvent dichloromethane gradually evaporates to obtain a masterbatch;
[0111] S3: The masterbatch is put into a single screw extruder for melt extrusion, and then put into a casting machine for casting molding, and then embossing, cooling, pulling and winding are performed in sequence to produce a light conversion solar cell encapsulation film with a thickness of 0.5 mm.
[0112] Application Example 7
[0113] The full-spectrum white light emitting carbon quantum dot solution obtained in Preparation Example 1 is used to prepare a light-converting solar cell encapsulation film, and the specific steps are as follows:
[0114] S1: Weigh the following raw materials in parts by weight: 100 parts of POE resin (melt index of 15 g / 10 min, melting point of 76°C), 0.05 parts of full-spectrum white light emitting carbon quantum dot solution (obtained in Preparation Example 1), 1.0 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.6 parts of triallyl isocyanurate, 0.3 parts of γ-methacryloxypropyltrimethoxysilane, 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacate, and 0.1 parts of antioxidant 1076;
[0115] S2: Put all the raw materials into a mixing kettle, control the temperature at 45±5°C and stir and mix, so that the carbon quantum dots and other additives penetrate into the resin, and the low boiling point solvent dichloromethane gradually evaporates to obtain a masterbatch;
[0116] S3: The masterbatch is put into a single screw extruder for melt extrusion, and then put into a casting machine for casting molding, and then embossing, cooling, pulling and winding are performed in sequence to produce a light conversion solar cell encapsulation film with a thickness of 0.5 mm.
[0117] Application Example 8
[0118] The full-spectrum white light emitting carbon quantum dot solution obtained in Preparation Example 1 is used to prepare a light-converting solar cell encapsulation film, and the specific steps are as follows:
[0119] S1: Weigh the following raw materials in parts by weight: 100 parts of POE resin (melt index of 15 g / 10 min, melting point of 76°C), 0.05 parts of full-spectrum white light emitting carbon quantum dot solution (obtained in Preparation Example 1), 1.0 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.8 parts of triallyl isocyanurate, 0.5 parts of vinyl trimethoxysilane, 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacate, and 0.1 parts of antioxidant 1076;
[0120] S2: Put all the raw materials into a mixing kettle, control the temperature at 45±5°C and stir and mix, so that the carbon quantum dots and other additives penetrate into the resin, and the low boiling point solvent dichloromethane gradually evaporates to obtain a masterbatch;
[0121] S3: The masterbatch is put into a single screw extruder for melt extrusion, and then put into a casting machine for casting molding, and then embossing, cooling, pulling and winding are performed in sequence to produce a light conversion solar cell encapsulation film with a thickness of 0.5 mm.
[0122] Application Example 9
[0123] The full-spectrum white light emitting carbon quantum dot solution obtained in Preparation Example 1 is used to prepare a light-converting solar cell encapsulation film, and the specific steps are as follows:
[0124] S1: Weigh the following raw materials in parts by weight: 100 parts of EVA resin (melt index of 25 g / 10 min, melting point of 70°C), 0.05 parts of full-spectrum white light emitting carbon quantum dot solution (obtained in Preparation Example 1), 0.8 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.6 parts of triallyl isocyanurate, 0.3 parts of γ-methacryloxypropyltrimethoxysilane, 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacate, and 0.1 parts of antioxidant 1076;
[0125] S2: Put all the raw materials into a mixing kettle, control the temperature at 45±5°C and stir and mix, so that the carbon quantum dots and other additives penetrate into the resin, and the low boiling point solvent dichloromethane gradually evaporates to obtain a masterbatch;
[0126] S3: The masterbatch is put into a single screw extruder for melt extrusion, and then put into a casting machine for casting molding, and then embossing, cooling, pulling and winding are performed in sequence to produce a light conversion solar cell encapsulation film with a thickness of 0.5 mm.
[0127] Application Example 10
[0128] The full-spectrum white light emitting carbon quantum dot solution obtained in Preparation Example 1 is used to prepare a light-converting solar cell encapsulation film, and the specific steps are as follows:
[0129] S1: Weigh the following raw materials in parts by weight: 100 parts of EVA resin (melt index of 25 g / 10 min, melting point of 70°C), 0.05 parts of full-spectrum white light emitting carbon quantum dot solution (obtained in Preparation Example 1), 0.8 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.6 parts of triallyl isocyanurate, 0.3 parts of vinyl trimethoxysilane, 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacate, and 0.1 parts of antioxidant 1076;
[0130] S2: Put all the raw materials into a mixing kettle, control the temperature at 45±5°C and stir and mix, so that the carbon quantum dots and other additives penetrate into the resin, and the low boiling point solvent dichloromethane gradually evaporates to obtain a masterbatch;
[0131] S3: The masterbatch is put into a single screw extruder for melt extrusion, and then put into a casting machine for casting molding, and then embossing, cooling, pulling and winding are performed in sequence to produce a light conversion solar cell encapsulation film with a thickness of 0.5 mm.
[0132] Comparative application example 1
[0133] The light-converting solar cell encapsulation film is prepared by the following steps:
[0134] S1: Weigh the following raw materials in parts by weight: 100 parts of POE resin (melt index of 15 g / 10 min, melting point of 76°C), 1.0 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.8 parts of triallyl isocyanurate, 0.5 parts of γ-methacryloxypropyltrimethoxysilane, 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacate, and 0.1 parts of antioxidant 1076;
[0135] S2: Put all the raw materials into a mixing kettle, control the temperature at 45±5°C and stir and mix, so that the carbon quantum dots and other additives penetrate into the resin, and the low boiling point solvent dichloromethane gradually evaporates to obtain a masterbatch;
[0136] S3: The masterbatch is put into a single screw extruder for melt extrusion, and then put into a casting machine for casting molding, and then embossing, cooling, pulling and winding are performed in sequence to produce a light conversion solar cell encapsulation film with a thickness of 0.5 mm.
[0137] Comparative Application Example 2
[0138] The light-converting solar cell encapsulation film is prepared by the following steps:
[0139] S1: Weigh the following raw materials in parts by weight: 100 parts of EVA resin (melt index is 25g / 10min, melting point is 70°C), 0.8 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.6 parts of triallyl isocyanurate, 0.3 parts of γ-methacryloxypropyltrimethoxysilane, 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacate, and 0.1 parts of antioxidant 1076;
[0140] S2: Put all the raw materials into a mixing kettle, control the temperature at 45±5°C and stir and mix, so that the carbon quantum dots and other additives penetrate into the resin, and the low boiling point solvent dichloromethane gradually evaporates to obtain a masterbatch;
[0141] S3: The masterbatch is put into a single screw extruder for melt extrusion, and then put into a casting machine for casting molding, and then embossing, cooling, pulling and winding are performed in sequence to produce a light conversion solar cell encapsulation film with a thickness of 0.5 mm.
[0142] Comparative Application Example 3
[0143] The full-spectrum white light emitting carbon quantum dot solution obtained in Comparative Preparation Example 1 was used to prepare a light-converting solar cell encapsulation film, and the specific steps are as follows:
[0144] S1: Weigh the following raw materials in parts by weight: 100 parts of POE resin (melt index of 15 g / 10 min, melting point of 76°C), 0.05 parts of full-spectrum white light emitting carbon quantum dot solution (obtained from Comparative Preparation Example 1), 1.0 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.8 parts of triallyl isocyanurate, 0.5 parts of γ-methacryloxypropyltrimethoxysilane, 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacate, and 0.1 parts of antioxidant 1076;
[0145] S2: Put all the raw materials into a mixing kettle, control the temperature at 45±5°C and stir and mix, so that the carbon quantum dots and other additives penetrate into the resin, and the low boiling point solvent dichloromethane gradually evaporates to obtain a masterbatch;
[0146] S3: The masterbatch is put into a single screw extruder for melt extrusion, and then put into a casting machine for casting molding, and then embossing, cooling, pulling and winding are performed in sequence to produce a light conversion solar cell encapsulation film with a thickness of 0.5 mm.
[0147] Comparative Application Example 4
[0148] The full-spectrum white light emitting carbon quantum dot solution obtained in Comparative Preparation Example 2 was used to prepare a light-converting solar cell encapsulation film, and the specific steps are as follows:
[0149] S1: Weigh the following raw materials in parts by weight: 100 parts of POE resin (melt index of 15 g / 10 min, melting point of 76°C), 0.05 parts of full-spectrum white light emitting carbon quantum dot solution (obtained from Comparative Preparation Example 2), 1.0 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.8 parts of triallyl isocyanurate, 0.5 parts of γ-methacryloxypropyltrimethoxysilane, 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacate, and 0.1 parts of antioxidant 1076;
[0150] S2: Put all the raw materials into a mixing kettle, control the temperature at 45±5°C and stir and mix, so that the carbon quantum dots and other additives penetrate into the resin, and the low boiling point solvent dichloromethane gradually evaporates to obtain a masterbatch;
[0151] S3: The masterbatch is put into a single screw extruder for melt extrusion, and then put into a casting machine for casting molding, and then embossing, cooling, pulling and winding are performed in sequence to produce a light conversion solar cell encapsulation film with a thickness of 0.5 mm.
[0152] Test Case
[0153] The performance tests of the films prepared in each application example and comparative application example are as follows:
[0154] (1) Transmittance test: The film to be tested is stacked according to the structure of glass / high-temperature cloth / film / high-temperature cloth / backboard, and placed in a lamination machine for lamination. After the lamination, the high-temperature isolation cloth is removed and the transmittance in the range of 380-1100nm is tested using a UV spectrophotometer.
[0155] (2) UV resistance test: The film to be tested is stacked according to the glass / film / backboard structure, placed in a lamination machine for lamination, cooled to obtain a sample, and placed in a UV accelerated aging chamber at a temperature of 55-65°C, a wavelength of 280-400nm, and an irradiation of 60KWh / m 2 After the aging process is completed, the change in the yellowness index before and after aging is tested.
[0156] (3) Power and power generation test: Use adhesive films of specific sizes to assemble and laminate solar cells into crystalline silicon photovoltaic modules with a rated power of 250W. The module power test is carried out under the irradiation of standard light sources (400-1100nm) without UV rays and simulated sunlight (280-1100nm).
[0157] In the above three tests, the lamination process parameters are temperature 145℃, vacuum 5min, pressurization 1min, and pressure holding 12min. The test results are shown in Table 1.
[0158] Table 1
[0159]
[0160] It can be seen from Table 1 that:
[0161] (1) Compared with Comparative Application Example 1, carbon quantum dots are added to Application Examples 1-3, and the transmittance and ultraviolet yellowing degree of the adhesive film are close to those of Comparative Application Example 1, while the module power under 280-1100nm light source irradiation is significantly higher than that of Comparative Application Example 1 (for photovoltaic modules, it is difficult to increase the power, and an increase of 2-3w is of great value). Compared with Comparative Application Example 2, carbon quantum dots are added to Application Example 9, and the transmittance and ultraviolet yellowing degree of the adhesive film are close to those of Comparative Application Example 2, while the module power under 280-1100nm light source irradiation is significantly higher than that of Comparative Application Example 2. The above results show that the use of full-spectrum white light emitting carbon quantum dots in the present invention can effectively improve the utilization efficiency of solar cells for sunlight, and will not cause excessive impact on the transmittance and light stability of the encapsulation adhesive film.
[0162] (2) Compared with comparative application examples 3 and 4, the component power of application example 1 under 280-1100nm light source irradiation is higher. The reason is that the carbon quantum dots obtained in comparative preparation examples 1 and 2 cannot emit white fluorescence under ultraviolet light irradiation, while the carbon quantum dots obtained in preparation example 1 can convert ultraviolet light into 400-700nm full-spectrum white light. Therefore, compared with comparative preparation examples 1 and 2, the carbon quantum dots obtained in preparation example 1 are applied to the encapsulation film, which can improve the film's utilization efficiency of sunlight to a greater extent.
[0163] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0164] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A light-converting solar cell encapsulation film, characterized in that: The light-converting solar cell encapsulation film contains full-spectrum white light emitting carbon quantum dots; the preparation method of the full-spectrum white light emitting carbon quantum dots comprises the following steps: (1) dissolving p-phenylenediamine in anhydrous ethanol to prepare a p-phenylenediamine ethanol solution with a concentration of 1-5 wt%; (2) subjecting the p-phenylenediamine ethanol solution to a solvothermal reaction at 175-185° C. for 10-13 hours to obtain a reaction mixture; (3) Using a mixture of methanol and dichloromethane in a volume ratio of 1:3.5-4.5 as an eluent, the reaction mixture is separated and purified by a gel permeation chromatography column, and the obtained eluate is extracted with water to obtain a dichloromethane solution containing full-spectrum white light emitting carbon quantum dots.
2. The light-converting solar cell encapsulation film according to claim 1, characterized in that: In step (3), the filler in the gel permeation chromatography column is silica gel with a mesh size of 200-300 meshes.
3. The light-converting solar cell encapsulation film according to claim 1, characterized in that: After step (3), the solvent in the dichloromethane solution containing the full-spectrum white light emitting carbon quantum dots is evaporated to obtain the full-spectrum white light emitting carbon quantum dot powder.
4. The light-converting solar cell encapsulation film according to any one of claims 1 to 3, characterized in that: The raw materials of the light-converting solar cell encapsulation film include the following components in parts by weight: 100 parts of base resin, 0.05-0.5 parts of full-spectrum white light emitting carbon quantum dot solution, and 0.1-2 parts of a cross-linking agent.
5. The light-converting solar cell encapsulation film according to claim 4, characterized in that: In the full-spectrum white light emitting carbon quantum dot solution, the content of the full-spectrum white light emitting carbon quantum dots is 3-10wt%.
6. The light-converting solar cell encapsulation film according to claim 4, characterized in that: The raw materials of the light-converting solar cell encapsulation film also include the following components in parts by weight: 0.1-2 parts of a cross-linking agent, 0.1-2 parts of a coupling agent, 0.01-1 parts of a light stabilizer, and 0.01-2 parts of an antioxidant.
7. The light-converting solar cell encapsulation film according to claim 4, characterized in that: The base resin is one or more of ethylene-vinyl acetate copolymer, ethylene-octene copolymer, ethylene-butene copolymer, ethylene-methyl methacrylate copolymer and polyvinyl butyral.
8. The light-converting solar cell encapsulation film according to claim 6, characterized in that: The light stabilizer is one or more of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol) succinate and bis(2,2,6,6-tetramethyl-4-piperidinol) sebacate.
9. A method for preparing a light-converting solar cell encapsulation film according to any one of claims 4 to 8, characterized in that: The following steps are involved: S1: Mix all raw materials and remove the solvent to obtain masterbatch; S2: Extruding and molding the masterbatch to obtain a light-converting solar cell encapsulation film.
10. The preparation method according to claim 9, characterized in that: The solvent in the full-spectrum white light emitting carbon quantum dot solution is dichloromethane; in step S1, the method of mixing and removing the solvent is stirring at 40-50°C.
Citation Information
Patent Citations
Preparation method of carbon quantum dot-based fluorescence film giving out orange-red light
CN106992240A
Single-component white light carbon quantum dots, preparation method thereof and luminescent devices
CN110846030A
Cited By
Light conversion material, preparation method and application of light conversion material in photovoltaic adhesive film
CN117025198A